Pepper casenitizer / Nurfatihah Syahirah Zaidi Rahimy ... [et al.] - Zaidi Rahimy, Nurfatihah Syahirah; Mohamad Shahril, Syahira Nisha Nabila; Rosli, Muhammad Afiq Syahmi; Yaman, Nur Wani Syamimi; Gatu, Alvin (2021)
Crimes in Malaysia are always a serious subject matter. Crime in our society such as sexual assault is known worldwide hence it increases the level of fear. Therefore, Pepper Casenitizer is a one-step solution or prevention product in ensuring the safety of users from being a victim of assaults and protection from germs. The objectives of creating this product are to protect your phone from scratch, to act as a protection from any threats, and to ensure users have their carry-on hygienic equipment. The idea of this product is an innovation combining 3 items, which are the pepper spray that acts as the defense mechanism, hand sanitizer that acts as the hygiene purpose, and a phone casing that acts as the phone holder. The speciality of this product is it can be customizable to suit the user's personality and has refillable pepper spray and hand sanitizer. This phone case is convenient as it is attached to the phone case, and the users do not need to worry about bringing it anywhere as the product is 3in1. The users can pull out the phone case to use it as protection when they are facing danger. It is also convenient to have this phone case as it has hand sanitizer to keep your hands clean. The target market is for any gender as every individual needs to be aware of safety and hygiene on a daily basis. The users need to insert both pepper spray and hand sanitizer inside in the spray compartment. The mist has to be activated by pressing the activator button to release the mist. With all three elements combined, this product can provide good protection from dangers and germs.